PELATIHAN DAUR ULANG SAMPAH PLASTIK UNTUK MENGOPTIMALKAN KEGIATAN EKSTRAKURIKULER MAHASISWA PROGRAM STUDI BIOLOGI - Lisye Iriana Zebua (JURNAL PENGABDIAN PAPUA, 2017)
Trash is a wasted or discarded material  from the source of human activities and natural processes that do not have economic value. The plastic waste is the largest number of waste from human because many people are using plastic for everyday life. Everyone, when plastic shopping will definitely need to bring groceries. If the plastic is not used normally people would throw it into the trash, to the river, to the ground, or even burned directly. Until now, the students of Biology not thought to try the plastic waste recycling. This is due to limited knowledge and skills of the students in Department of Biology on recycling of plastic waste. Therefore, the training and practice of recycling plastic waste needs to be done as one of concern for students from the Department of Biology to supports the government programs paid on plastic bags. The activity methods used are observation and practice in the field by collecting and utilizing waste plastic household scale (eg: plastic refill fragrances, clothing, soap, and dishwashing soap) that exist in the environment. The students will create a straight pattern bag with a variety of innovations models. The bag can serve as a shopping cart bag with a variety of sizes. The end result of this activity is the creation of product innovation models of multi-functional shopping cart bags are environmentally friendly. In addition, with the end of the training activity, the knowledge and care about environmental of the students are growing more higher. Keywords: training, recycling, plastic waste, students of Department of Biology